Internalisasi Keadilan Substantif dalam Pembagian Waris Ab-intestato Antara Anak Kandung dan Anak Perkawinan Kedua Melalui Analisis Yuridis Putusan Pengadilan Negeri Pekanbaru 79/Pdt.G/2016/PN Pbr - Rayi Kharisma Rajib; Putri Grace Sapnawati Banjarnahor; Triswa Muthia Hanifah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
A Discussion on the Internalization of Substantive Justice in the Distribution of an Intestate Estate Between Biological Children and Children from a Second Marriage Through a Legal Analysis of the Pekanbaru District Court Decision No. 79/Pdt.G/2016/PN Pbr Using a Normative Legal Approach and a Literature Review. The occurrence of a second marriage does not diminish the rights of the first child to receive an inheritance from a decedent who has died intestate under the Civil Code. As long as there is a blood relationship with the decedent, both children from different marriages are entitled to receive the inheritance without exception. If this right is violated, the violating party may be sued and face sanctions. The state plays a crucial role in protecting inheritance rights to ensure they are fulfilled.